Brand Image and Purchase Decisions: Consumer Social Values in Green Marketing - Adiyanto, Yoga; Ibrahim, Mukdad; Dharmawan, Dhany Isnaeni; Khofin, Kiki; Sunaryo, Deni (Faculty of Economics and Business | Universitas Diponegoro, 2025)
This study examines the relationship between brand image, consumer social values, and purchase decisions within the context of green marketing for electric motorcycles. Specifically, it explores how the Indonesian government’s vision for environmental sustainability aligns with consumer values and influences their purchase behavior. The research employs both qualitative and quantitative methods, collecting data through surveys and in-depth interviews to understand the key drivers behind consumer purchasing decisions for electric motorcycles in Indonesia. Findings indicate that consumers are increasingly considering environmental impact, alongside brand image, when making purchase decisions. Moreover, government policies promoting green initiatives further enhance consumer willingness to engage with electric motorcycle brands. This paper offers valuable insights for marketers looking to leverage green marketing strategies in the rapidly growing electric vehicle sector in Indonesia.